2020
DOI: 10.3390/geriatrics5030048
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Aerobic Exercise Diminishes the Effects of Sarcopenia in Senescence-Accelerated Mice Prone8 Model

Abstract: Loss of muscle mass and strength are progressing with aging. Exercise is a beneficial method to prevent physical dysfunction, and habitual exercise can improve the muscle quality. Therefore, we evaluated the effects of long-term habitual exercise’s impact on sarcopenia utilizing the senescence-accelerated mice prone8 (SAMP8) model. Notably, 27 w SAMP8 were used in this study. Mice were classified into 28 (28 w) and 44 weeks old. The 44-week group was divided into the sedentary group (44 w) and a group exercisi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Other strengths are the analysis of the effects of the treatments alone or in combination with each other and the use of female mice. Most of the previous studies to date regarding sarcopenia and aging, as well as n -3 PUFA supplementation and exercise, have been carried out in male mice [ 35 , 36 , 37 ], which was one of the reasons for choosing females in this study. However, it is important to consider that some studies have reported metabolic differences between male and female mice during aging and obesity [ 140 ] and therefore the use of only female mice could also be seen as a limitation, since results could vary between sexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other strengths are the analysis of the effects of the treatments alone or in combination with each other and the use of female mice. Most of the previous studies to date regarding sarcopenia and aging, as well as n -3 PUFA supplementation and exercise, have been carried out in male mice [ 35 , 36 , 37 ], which was one of the reasons for choosing females in this study. However, it is important to consider that some studies have reported metabolic differences between male and female mice during aging and obesity [ 140 ] and therefore the use of only female mice could also be seen as a limitation, since results could vary between sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, few studies to date have addressed the potential beneficial effects of long-term consumption of n -3 PUFA coupled with physical exercise in the context of aging and obesity [ 31 , 32 , 33 , 34 ]. In addition, most of the studies analyzing the effects of n -3 PUFA or exercise on sarcopenia have been conducted in male mice [ 35 , 36 , 37 ]. In this respect, we have recently reported that a 16-week resistance training (RT) program (alone or in combination with Docosahexaenoic acid (DHA)) improved the lower and upper limb muscle strength and quality in overweight/obese postmenopausal women [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when SAMP8 mice are used to study sarcopenia, they are mostly used at 8 months of age and later. Many studies have used SAMP8 mice to validate the effect of exercise intervention on sarcopenia and to assess its intervention effect 65,66 . For example, Takigawa et al 65 .…”
Section: Classification Of Mouse Models Of Sarcopeniamentioning
confidence: 99%
“…Exercise has been shown to induce various physiological and biochemical changes within the body. Exercise therapy has been explored for the management of dementia, weak locomotion-associated sarcopenia, and diabetes [1][2][3][4][5][6]. Several studies have demonstrated the effects of exercise on various organs, and, more recently, its effects on the small intestine have also been reported [7,8].…”
Section: Introductionmentioning
confidence: 99%